PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE QUICK ON THE DRAW (QoD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Fitri Apriliyani; Salahudin, Anas; Yanuar Rahman, Alvin (Universitas Islam Malang, 2024)
This study was conducted to determine whether the application of the Quick on The Draw (QoD) type learning model can improve student learning outcomes in science subjects in class IV MI. The research method used in this research is Classroom Action Research (CAR). The data collection technique used is using teacher and student observation sheets and learning outcomes assessment in the form of description and short answer tests. Based on the results of the research that has been done, the research shows that the application of the Quick on The Draw (QoD) type learning model runs well. This can be seen from the increasing classical completeness of students' cognitive learning outcomes in each cycle. The increase experienced was obtained through the results of students' cognitive learning tests in each action. The completeness of students' cognitive learning outcomes in cycle I action I the percentage of classical learning outcomes was at 36% while in cycle I action II the percentage of classical learning outcomes increased to 56%. In cycle II action I the percentage of students' classical learning completeness increased to 84% while in cycle II action II it increased to 92%. So with this it can be concluded that there is an increase in student learning outcomes on energy transformation material by applying the Quick on The Draw (Qod) learning model for grade IV students of MI. Key words: cooperative learning, quick on the draw (QoD), students cognitive learning